Aflatoxin Detoxification by Biosynthesized Iron Oxide Nanoparticles Using Green and Black Tea Extracts - Hasan Gedikli; Arda Akdogan; Omer Karpuz; Osman Akmese; Havva Nur Kobya; Cemalettin Baltaci (BioResources, 2023)
Researchers have recently been interested in employing nanoparticles (NPs) obtained from herbal extracts through green synthesis for various applications. This study investigated the detoxification of aflatoxins, which are toxic substances produced by molds Aspergillus flavus and Aspergillus parasiticus. The present work examined the levels of aflatoxins in hazelnut and peanut puree. Turkish black tea extract (BTE), Turkish green tea extract (GTE), green synthesized black tea-based iron oxide nanoparticles (BTFeONPs), and green tea-based iron oxide nanoparticles (GTFeONPs) were produced for aflatoxin removal. Characterizations and various antioxidant and antimicrobial activities of the tea extracts and iron oxide nanoparticles (FeONPs) were investigated. The aflatoxin levels of hazelnut puree used for this study were 6.57 ± 0.06 µg/kg for aflatoxin B1 and 13.03 ± 0.16 µg/kg for total aflatoxin, whereas the aflatoxin levels of (AFLB1) peanut puree were 7.79 ± 0.15 µg/kg for AFLB1 and 15.21 ± 0.12 µg/kg for total aflatoxin. Using soluble BTE resulted in a 40 to 50% decrease in aflatoxin levels in hazelnut and peanut purees, while soluble GTE led to a 30 to 45% decrease. Meanwhile, using BTFeONPs and GTFeONPs resulted in a 33 to 48% and 40 to 50% decrease, respectively, in aflatoxin levels in hazelnut and peanut purees.